Middle East Respiratory Syndrome Coronavirus (MERS-CoV) is Not Circulating Among Hajj Pilgrims - Jaffar A. Al-Tawfiq; Ziad A. Memish (Springer, 2023)
Abstract Since the emergence of the middle east respiratory syndrome coronavirus (MERS-CoV) 2012, the virus had caused multiple healthcare-associated outbreaks. The initial 2012 Hajj season started few weeks after the first case of MERS-CoV, but there were no reported cases among pilgrims in 2012. Since then, there had been multiple studies examining the prevalence of MERS-CoV among Hajj pilgrims. Subsequently, multiple studies utilized screening of pilgrims for MERS-CoV and > 10,000 pilgrims were screened with no identifiable cases of MERS.